Fractious Form: The Trans/Mutable Post-Apartheid Novel - Barris, Ken (Department of English Language and Literature, 2014)
The question which I explore is to what degree, and in what way, the paradigm of anti-apartheid literature gives way to its post-apartheid successor. More particularly, I explore how post-apartheid South African novels perpetuate, displace or transmute the narrative forms and conventions characteristic of anti-apartheid writing. I therefore read the forms and conventions in certain post-apartheid novels through the lens of anti-apartheid discourse, in particular its demand for politically engaged realism, tracing continuity and change. I argue that The Good Doctor (2003) by Damon Galgut and Karoo Boy by Troy Blacklaws (2004) reiterate anti-apartheid conventions through devices that become anachronistic, in that they reproduce antiapartheid literary dynamics without adaptation to the post-apartheid conditions represented or implied in these texts. Formal reinvention, however, is evident in the following novels. In The Restless Supermarket (2002), Ivan Vladislavi displaces political engagement from narrative form into the speech acts of his narrator. This text thereby stages a lexical meditation that displaces the typical realist sequence of symptomatic events. Despite this innovation, there are continuities between his work and the early writing of J.M. Coetzee, which suggest that Coetzee anticipated characteristic post-apartheid narrative strategies ahead of their time. Further, the innovative magic realist forms of Zakes Mda's Ways of Dying (1995) and Phaswane Mpe's Welcome to Our Hillbrow (2001) engage with crises of transition so dire that death becomes their central metaphor. Both writers introduce the device of orature as assertions of African identity. However, Mda counterposes orature against death, injecting through it a humanising principle. In Mpeâs novel, by contrast, orature acquires a murderous agency. I trace variants of what I term "fractured form", namely form that is duplicitous, or otherwise dualistic, through a further group of novels. My premise is that the social fracture represented as content scripts the formal fracture/fractiousness in their narrative forms. An attendant property is to disrupt nationalist discourse in its dominant post-apartheid manifestation, namely the rainbow nation mythos. The texts in this group are Disgrace (1999) by J.M. Coetzee, David's Story (2000) by Z Wicomb, Achmat Dangor's Bitter Fruit (2001), Zakes Mda's The Madonna of Excelsior (2002), and What Kind of Child (Barris 2006). In conclusion, the central question to which I attend has been raised by Michael Green (1997: 7), namely how a body of texts generated within the episteme of anti-apartheid can be meaningfully related to the literary paradigm that replaces it. I find that in the collective formal inventions, fractures and displacements demonstrated in this thesis, an emergent post-apartheid episteme becomes discernable.